Cost-constrained selection of strand diameter and number in a litz-wire transformer winding. - Sullivan, C.R.
Design of litz-wire windings subject to cost constraints is analyzed. An approximation of normalized cost is combined with analysis of proximity effect losses to find combinations of strand number and diameter that optimally trade off cost and loss. The relationship between wire size, normalized cost, and normalized loss is shown to have a general form that applies to a wide range of designs. A practical design procedure is provided, Applied to an example design, it leads to less than half the original loss at lower than the original cost, or, alternatively, under one fifth the original cost with the same loss as the original design
Keywords: Cost-constrained selection; Eddy currents losses; Inductors; Litz-wire transformer winding; Loss reduction; Power conversion; Power transformers; Proximity effect; Proximity effect losses; Skin effect; Strand diameter; Strand number